ENGLISH INTERFERENCE IN BAHASA INDONESIA: A PHONOLOGY-TO-ORTHOGRAPHY CASE IN INSTAGRAM CAPTION - Laila Ulsi Qodriani (Universitas Muhammadiyah Semarang, 2019)
In January 2019, We Are Social Institutes has claimed that 150 million of Indonesian people use social media actively and excessively. This also proves that computer-mediated-communication (CMC) become an alternative way to interact in nowadays society. Instagram, as one of social media users’ favorite, shows a unique language phenomenon upon its ‘caption’. The language used by the users indicates the English interference toward Bahasa Indonesia has manifested from phonologically to orthographically since social media communication transforms the face-to-face interaction into written form. Based on the study in one of Instagram gossip account named @Lambe_Turah, it can be seen that the trend of inserting English influence in Instagram caption represented in some phonological rules, they are omission, assimilation, substitution, and epenthesis.